If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3x + -5x + y + 6y + -4y + 7 = 0 Reorder the terms: 7 + x + 3x + -5x + y + 6y + -4y = 0 Combine like terms: x + 3x = 4x 7 + 4x + -5x + y + 6y + -4y = 0 Combine like terms: 4x + -5x = -1x 7 + -1x + y + 6y + -4y = 0 Combine like terms: y + 6y = 7y 7 + -1x + 7y + -4y = 0 Combine like terms: 7y + -4y = 3y 7 + -1x + 3y = 0 Solving 7 + -1x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -1x + -7 + 3y = 0 + -7 Reorder the terms: 7 + -7 + -1x + 3y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x + 3y = 0 + -7 -1x + 3y = 0 + -7 Combine like terms: 0 + -7 = -7 -1x + 3y = -7 Add '-3y' to each side of the equation. -1x + 3y + -3y = -7 + -3y Combine like terms: 3y + -3y = 0 -1x + 0 = -7 + -3y -1x = -7 + -3y Divide each side by '-1'. x = 7 + 3y Simplifying x = 7 + 3y
| (72x-54y)-(49x+6y)= | | 2x+8+52+8=60 | | -19r+17r+3r+r=-10 | | 5(3x-6)=14x+14 | | -2(2y-7)+3y=14 | | 2x+8+52+8=180 | | 1.2x-4+1=-3-1.2x | | 25t=15 | | 20-(3x-4)=33 | | 2/3×10 | | X-7=9-7x | | -30-7y+27=15 | | -2(2y+7)+3=14 | | 3[(2c)-4-(-c)+3]=2c+4 | | 1/6b=12 | | y=-8x+24 | | 73=25x^(1/3) | | x=2-(8/x) | | 3x^2=-77+18x | | 8-8x=8+x+4-8x | | -k=9k-10 | | 40r^2-3yt+24ry-5rt=0 | | 126x+292y=20150 | | -6m-1=24 | | 3h-18/9 | | -2a+8+a+(-3)=2+(-2a)+(-a)+3 | | 416=x-7(-3x-32) | | -3/4k+2=10 | | 5x=(-45) | | 0.4y=50 | | 48m+36=6(3m-19) | | 4x+6.25=44.25 |